Systematic review and network meta-analysis of the effects of bioactive compounds on pain intensity and quality of life in neuropathic pain patients - Tang, Rong; Gong, Chao-Yang; Liu, Yu-Qian; Wang, Yingbin; Zhou, Hai-Yu (Frontiers in Pharmacology, 2025)
BackgroundIn recent years, a significant number of researchers have concentrated on bioactive compounds for the treatment of neuropathic pain. However, there remains a lack of compelling evidence to robustly support their therapeutic efficacy.ObjectiveThis study aims to assess the impact of various bioactive compounds on pain intensity and quality of life in patients suffering from neuropathic pain by conducting a network meta-analysis.MethodsResearchers conducted a systematic search across five electronic databases—PubMed, EMBASE, Cochrane Library, the Cochrane Central Register of Controlled Trials, and Web of Science—from the inception of each database until April 2025. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias assessment tool. Data analysis was subsequently performed using Stata MP 15.1 software. The primary outcome measures consisted of the following standardized assessment scales: Visual Analogue Scale (VAS), Neuropathic Pain Scale (NPS), Hospital Anxiety and Depression Scale (HADS), Patient Global Impression of Change (PGIC), and Leeds Sleep Evaluation Questionnaire (LSEQ). Treatment effects were ranked based on probability values derived from the Surface Under the Cumulative Ranking Curve (SUCRA).ResultsFollowing the screening process, 20 eligible randomized controlled trials were included, involving a total of 2,471 patients and evaluating six distinct bioactive compound-based therapeutic interventions. The ranking of treatments, based on SUCRA values, indicated that tetrahydrocannabinol was associated with the highest likelihood of being the most effective option for reducing VAS scores (SUCRA: 88.2%). Furthermore, it consistently ranked favorably across other outcomes, including NPS (84.8%), PGIC (85.1%), and LSEQ (90.7%). Capsaicin was ranked as the most promising intervention for improving HADS scores (90.1%).ConclusionThis study offers valuable insights into the application of bioactive compounds for the management of neuropathic pain. However, the research also presents certain unavoidable limitations, such as heterogeneity among studies and the absence of direct comparative evidence for specific intervention measures. Future studies should include larger sample sizes, extended follow-up periods, and more rigorously designed randomized controlled trials to definitively establish the efficacy of bioactive compounds in patients with neuropathic pain patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD420251041801.